2017
DOI: 10.1080/00365521.2017.1350284
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of foreign bodies in the upper gastrointestinal tract: a retrospective study of 1294 cases

Abstract: Delayed flexible endoscopy in patients, especially elderly patients, with sharp FB impactions in the esophagus results in worse endoscopic outcomes. Endoscopic management under general anesthesia did not improve the therapeutic results compared with topical pharyngeal anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 21 publications
5
70
2
2
Order By: Relevance
“…13 That study included minor haematomas and ulcerations as complications, which justify the higher complication rate. However, we consider that minor endoscopic findings should not be reported as complications because they will not alter management in the majority of cases, as also suggested by the American Society of Gastrointestinal Endoscopy (ASGE).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 That study included minor haematomas and ulcerations as complications, which justify the higher complication rate. However, we consider that minor endoscopic findings should not be reported as complications because they will not alter management in the majority of cases, as also suggested by the American Society of Gastrointestinal Endoscopy (ASGE).…”
Section: Discussionmentioning
confidence: 99%
“…This estimate of 80% is based on old studies performed before the era of flexible endoscopy and when conservative treatment was the preferred management. 11,12 In addition, most of the recent studies on this topic include only patients with confirmed foreign body presence at endoscopy, 13 and so the proportion of patients with FBI in whom the foreign body will be encountered at endoscopy is not precisely known. Thus it is important to assess the proportion of patients with FBI in which the foreign body is encountered at endoscopy and also to identify predictors for its presence, because it can identify patients with a higher probability of actually having a foreign body in the upper digestive tract, and it can modify the threshold to perform endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in Asia and coastal countries reported that bone fragments, especially fish bones, are most commonly encountered. 3,12,13,16,18,24 While studies in the United States showed that meat comprised the majority type. 13,25 A systematic review including 13 092 patients all over the world revealed sharp-pointed FB (38.1%) as the most common FB.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the inappropriate interventions by patients may worsen the condition. For example, trying to remove a foreign object by bolus ingestion of food may worsen the gastrointestinal trauma [8]. Therefore it should be recognized that pointed objects, long foreign bodies, and the presence of complications are important risk factors for further complications [7].…”
Section: Discussionmentioning
confidence: 99%